Topologically Organized Networks in the Claustrum Reflect Functional Modularization - Ham, Gao Xiang; Augustine, George J. (Frontiers in Neuroanatomy, 2022)
Using genetic strategies and viral-based directional tracers, we investigated the topological location and output networks of claustrum (CLA) neuron populations projecting to either retrosplenial cortex, primary motor cortex or to basolateral amygdala. We found that all 3 CLA neuron populations clearly reside in distinct topological locations within the CLA complex and project broadly to multiple downstream targets. Each neuron population projects to different targets, suggesting that each CLA subzone coordinates a unique set of brain-wide functions. Our findings establish that the claustrum complex encompasses at least 3 minimally overlapping networks that are compartmentalized into different topological subzones. Such modularity is likely to be important for CLA function.